Chemical Ordering in In-Sn Liquid Alloy - Adhikari, D (Nepal Journal of Science and Technology, 2014)
Quasi-chemical expression has been used for weakly interacting compound forming binary alloy to obtain energy parameters and their temperature derivative for In-Sn liquid alloy at 700 K. These energy parameters have then been used to calculate thermodynamic functions, such as free energy of mixing, heat of mixing, entropy of mixing and microscopic functions, such as concentration fluctuation in long wavelength limit, Warren-Cowely short range order parameter. The analysis reveals that the energy parameters are temperature dependent and the In-Sn liquid alloy at 700 K is weakly interacting heterocoordination system. The observed thermodynamic properties of In-Sn alloy in molten state have been successfully explained by assuming 3 In Sn complex on the basis of the quasichemical formalism for weakly interacting system. DOI: http://dx.doi.org/10.3126/njst.v14i2.10431 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 161-164